Działalność Urzędu do Spraw Wyznań w zakresie tworzenia i obsady stanowisk kościelnych: Operations of the Office for the Proclamation of Faith concerning the creation and occupation of church positions - Krawczyk, Michał (Management and Administration Journal, 2021)
The article presents, on the base of published as well as unpublished archival sources, the involvement of the Office for the Proclamation of Faith (the central organ of administration concerning religious confession in the Polish People’s Republic) in the creation and occupation of church positions.